Bioactive Molecules from Extreme Environments (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The papers included in this Special Issue "Bioactive Molecules from Extreme Environments" provide an overview of the growing interest in species biodiversity, highlighting the importance of marine extreme environments as sources of a unique marine chemical diversity of molecules. It is worth noting that six articles in this Special Issue are focused on molecules and enzymes isolated from Antarctica. This means that there is a growing interest in this habitat, most probably due to being perceived as an important source of drug discovery. In fact, the unique environment and ecological pressures of marine polar regions might be the major drivers of a selection of unique biological communities that are able to biosynthesize new compounds with diverse biological activities. It is expected that, in the near future, more marine molecules from polar regions, as well as from other extreme habitats, will find their way into biomedical and biotechnological applications.